Economic impact and disease burden of COVID-19 in a tertiary care hospital: A three-year analysis - Kanerva, Mari; Rautava, Kalle; Kurvinen, Tiina; Marttila, Harri; Finnilä, Taru; Rantakokko-Jalava, Kaisu; Pietilä, Mikko; Mustonen, Pirjo; Kortelainen, Mika (PUBLIC LIBRARY SCIENCE, 2025)
Background The COVID-19 pandemic has increased morbidity and mortality, along with substantial economic repercussions for healthcare systems and communities worldwide. This study describes the costs incurred by one of the biggest university hospitals in Finland during the first three years of the pandemic, from 2020 to 2022.
Methods A retrospective analysis was conducted at a 950-bed tertiary care hospital, encompassing data from 2020 to 2022. Hospitalized COVID-19 cases were identified from an automated surveillance program that integrated microbiological and administrative data. Patient-level data, including hospitalization demographics, vaccination status, and outcomes, were collected. Billing costs, indirect costs, and operational data were obtained to assess hospital costs comprehensively.
Results During 2020-2022, 2 555 COVID-19-positive patients were treated at the hospital. Of them, 57% were hospitalized primarily for COVID-19 with the hospital billing costs of 14 492 399 (median 4 137 / patient), and 47% of these costs were due to intensive care. Including ER visits of COVID-19 outpatients, admission screening and isolation costs of COVID-19 positive patients hospitalized for other reasons and indirect expenses, the total costs reached 28 899 298 over three years. Additionally, the hospital incurred losses of income due to postponed elective surgeries.
Discussion The economic burden of COVID-19 at the considered university hospital was substantial. Intensive care costs were a significant driver. This study provides a comprehensive overview of the economic and disease burden of COVID-19 at a tertiary care hospital, highlighting the need for strategic planning and financial readiness to address the costs associated with pandemics.